Emerging links between homeostatic synaptic plasticity and neurological disease - Dickman, Dion; Wondolowski, Joyce (Frontiers in Cellular Neuroscience, 2013)
Homeostatic signaling systems are ubiquitous forms of biological regulation, having been studied for hundreds of years in the context of diverse physiological processes including body temperature and osmotic balance. However, only recently has this concept been brought to the study of excitatory and inhibitory electrical activity that the nervous system uses to establish and maintain stable communication. Synapses are a primary target of neuronal regulation with a variety of studies over the past 15 years demonstrating that these cellular junctions are under bidirectional homeostatic control. Recent work from an array of diverse systems and approaches has revealed exciting new links between homeostatic synaptic plasticity and a variety of seemingly disparate neurological and psychiatric diseases. These include autism spectrum disorders, intellectual disabilities, schizophrenia, and Fragile X Syndrome. Although the molecular mechanisms through which defective homeostatic signaling may lead to disease pathogenesis remain unclear, rapid progress is likely to be made in the coming years using a powerful combination of genetic, imaging, electrophysiological, and next generation sequencing approaches. Importantly, understanding homeostatic synaptic plasticity at a cellular and molecular level may lead to developments in new therapeutic innovations to treat these diseases. In this review we will examine recent studies that demonstrate homeostatic control of postsynaptic protein translation, retrograde signaling, and presynaptic function that may contribute to the etiology of complex neurological and psychiatric diseases.